Heaven and hell : a novel of a Manchukuo childhood - Takarabe, Toriko, 1933-2020 (University of Hawaiʻi Press, 2018)
"Takarabe Toriko's autobiographical novel Heaven and Hell is a beautiful, chilling account of her childhood in Manchukuo, the puppet state established by the Japanese in northeast China in 1932. As seen through the eyes of a precocious young girl named Masuko, the frontier town of Jiamusi and its inhabitants are by turns enchanting, bemusing, and horrifying. Takarabe skillfully captures Masuko's voice with language that savors Manchukuo's lush forests and vast terrain, but violence and murder are ever present, as much a part of the scenery as the grand Sungari River. Masuko recounts the "Heaven" of her early life in Jiamusi, a place so cold in winter her joints freeze as she walks to school. She accepts this world, with its gentle ways and terrible brutality, because it is the only home she has known. Masuko feels at ease wandering among the street vendors hawking their hot and sticky steamed cakes or watching the cook slaughter ducks for dinner, and takes pleasure in following the routines of her Chinese, Russian, and Japanese neighbors. Her world is shattered in 1945, when she and her family must flee their adopted home and struggle, along with other Japanese settlers, to return to Japan. This second half of the book, the "Hell" of refugee life, is heartbreaking and disturbing, yet described with ferocious honesty."--Publisher's description